APPLICATION OF TRANSANAL TUBE AFTER ANTERIOR RECTAL RESECTION: IMPACT ON PREVENTION OF "ACHILLES HEEL" IN COLORECTAL SURGERY - Hodžić, Edin; Pušina, Sadat; Mulabdić, Adi; Muhović, Samir; Šukić-Karalić, Ramajana; Džeko, Melika; Cerić, Timur (Sanamed, 2024)
Aim: The aim of our study was to investigate the potential reduction in the likelihood of anastomotic leakage occurrence in patients undergoing open anterior resection of the rectum without a protective stoma for stage III adenocarcinoma, by employing a transanal tube after performing stapled colorectal anastomosis.Results: Considering the influence of all included risk factors, male gender (p=0.032; OR=2.873) and patients with type 2 diabetes mellitus (p=0.033; OR=2.873) demonstrated an increased likelihood of anastomotic leakage, while the presence of a transanal tube (p=0.043; OR=0.349; 95% CI: 0.126, 0.966) was associated with a statistically significant reduction in the likelihood of anastomotic leakage. T-test revealed that patients with anastomotic leakage without a placed tube had a statistically significantly longer mean postoperative hospitalization (20.94 days) compared to those with a transanal tube (19.43 days) (t=2.375; p=0.025). Kaplan-Meier analysis didn’t show a statistically significant difference in the average estimated time to the occurrence of anastomotic leakage between patients without (3.86 days) and with a transanal tube (4.58 days) (p=0.057).Conclusion: Our study found that the placement of a transanal tube after colorectal anastomosis may be associated with a reduced likelihood of anastomotic leakage and shorter hospitalization in case leakage occurs. Additionally, although no statistically significant difference was found in the effect of the tube on the occurrence of anastomotic leakage depending on the presence of type 2 diabetes mellitus, the indication for its use in patients with type 2 diabetes mellitus may be of particular benefit.
Keywords: Equipment and supplies; postoperative complications; rectal neoplasms; surgical procedure